FEMINISM AND GENDER DISCRIMINATION IN NORTHEASTERN NIGERIA: A REVIEW - ANAS ABUBAKAR; AMINU ABDULLAHI SALE (International Studies Journal)
It is a universal fact that women, unlike men gender used to be marginalized, oppressed, abused, and deprived their socio-economic, educational, political and legal rights. This necessitated a broader global feminist movement to advocate for equal rights and opportunities of all genders. This paper titled "Feminism and Gender Discrimination in Northeast Nigeria: A Theoretical Perspective on Northeastern Nigeria" presents an attempt to examine the existing discrimination of women with regards to their socio-economic, political, educational and legal rights in Northeastern Nigeria.  The paper uses secondary source of data collection through major instruments such as textbooks, journals, online publications, among others, while content method of data analysis was explored in the analysis of the data collated. The research also employs Legal feminist theories as its theoretical framework. Some of the findings of the paper reveals that, religion, culture, societal division of labour, among other things, contribute a lot in promoting gender discrimination in Northeastern Nigeria. The paper recommends for a designed policy that is "northeastern-centric" in nature that would address a notion of "men gender naturally ahead"; strengthen the activities of nongovernmental organizations for their advocacy against gender discrimination, and so forth.